2011
DOI: 10.1182/blood-2011-01-331298
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation, phenotype, and function of interleukin-17–producing human Vγ9Vδ2 T cells

Abstract: IntroductionIL-17 is a cytokine that induces mobilization and activation of neutrophils and triggers the production of proinflammatory cytokines and chemokines by a broad range of cellular targets. 1 It is predominantly produced by ␣␤ T cells, but also by natural killer (NK) T cells, 2 ␥␦ T cells, 3 and other non-T cells, such as macrophages and neutrophils. 4,5 Differentiation of CD4 T cells producing IL-17 (Th17) is initiated in naive Th cells by antigen-specific stimulation in the presence of the polarizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
299
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(314 citation statements)
references
References 52 publications
(84 reference statements)
14
299
0
1
Order By: Relevance
“…7B). IL-17 was completely undetectable, even in gd T cell cultures containing IL-1b, which was previously shown to support differentiation of IL-17-producing Vg9Vd2 T cells (46).…”
Section: Purified Gd T Cells Expanded By Zoledronate Plus Il-2 In Thesupporting
confidence: 56%
See 2 more Smart Citations
“…7B). IL-17 was completely undetectable, even in gd T cell cultures containing IL-1b, which was previously shown to support differentiation of IL-17-producing Vg9Vd2 T cells (46).…”
Section: Purified Gd T Cells Expanded By Zoledronate Plus Il-2 In Thesupporting
confidence: 56%
“…IL-17 could not be detected in PBMCs or in purified gd T cells, even in the presence of IL-1b and IL-18, which have been implicated in the regulation of IL-17 production in humans and mice (46,53), respectively. The requirements for the differentiation of IL-17-producing human Vg9Vd2 T cells were defined recently (46).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, we next investigated whether cytokines known to induce IL-17 production in mature γδ T-cells also participate in the programming of the γδ17 effector fate. Previous work suggested that γδ17 cells differ from their Th17 counterparts in terms of cytokine requirements, with IL-1β, IL-21, and IL-23 implicated as drivers of IL-17 production by γδ17 cells, whereas IL-6 is a key cytokine for Th17 cells 1719, 3235 . Therefore, we assessed whether adding combinations of IL-1β, IL-21, and IL-23 to the KN6/MEF co-cultures could result in the functional programming of the γδ17-effector subtype.…”
Section: Resultsmentioning
confidence: 99%
“…Activated Vc9/Vd2 T cells in fact induce chemotaxis and phagocytosis of neutrophils [85,86], and in return microbial compounds released by neutrophils upon phagocytosis of different pathogens are sensed by Vc9/Vd2 T cells [9,10], suggesting an intimate crosstalk of the two cell types, typically leading to their mutual activation. However, recent supports also suggest that under certain conditions neutrophils may actually suppress Vc9/Vd2 T cell responses [87,88], indicative of a fine-tuned regulatory interplay between the two cell types depending on the microenvironment [89].…”
Section: Interaction With Neutrophils: Unexpected Generation Of Apclimentioning
confidence: 99%